Structured system design for blended technology in classroom - Hussain, Hanafizan (World Scientific and Engineering Academy and Society (WSEAS), 2008)
Course planning in universities involves balancing multiple objectives. Through years of experiences in face-to-face teaching, faculty members have generated a great deal of knowledge and skill, which is often categorized by automatic routines and tacit knowledge. The advent of web and the growing of multimedia technology in education industry are transforming the context. This paper proposed a structured design for blended technology in classroom which comprehensively represents the scenario pf face-to-face and delivery methods in higher education. It requires the use of new tools as well as the creation and transformation of artifacts. It also poses new problems that require new kinds of support and collaboration since the faculty members may lack the technical ability to create their own blended course classes.